Implementation of Good Governance in Local Government Systems in Indonesia - Ari Purwanti (Journal of Governance, 2022)
This paper discusses the application of government accounting to initiate good governance in local government. This paper initially describes good governance in regional financial management. Next are the regional government accounting standards and finally, the implementation and good governance of the regional government accounting system. Discussion on accrual-based government accounting. This study uses a qualitative approach with a descriptive method. This study indicates that the application of local government accounting is closely related to four governance arrangements, namely fairness, transparency, accountability, and responsibility. Good governance can be achieved by empowering systems and institutions based on laws and regulations. Good financial management and control based on the government accounting system is the main priority of action taken by the government. In the study, it can also be concluded that accrual-based accounting standards are one of the implementations of good governance in Indonesia's local government accounting system.